Ownership Structure and Debt Policy on Dividend Policy: The Mediating Role of Profitability - Benedikta Gracesella Sinurat; Jeudi A T P Sianturi; Saur Melianna Sipayung; Merry Anna Napitupulu (Fakultas Ekonomi Universitas Simalungun, 2026)
This study examines the effects of ownership structure and debt policy on dividend policy, with profitability serving as a mediating variable, among energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Ownership structure is measured through institutional ownership (IO) and public ownership (PO), while debt policy is proxied by the Debt-to-Asset Ratio (DAR), profitability by Return on Assets (ROA), and dividend policy by the Dividend Payout Ratio (DPR). Using purposive sampling, 20 companies were selected over four years, yielding 80 panel observations. Data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) via WarpPLS 8.0. Findings indicate that institutional ownership exerts no significant influence on profitability or dividend policy, whereas public ownership and debt policy negatively and significantly affect both. Profitability positively and significantly predicts dividend policy. Mediation tests confirm that profitability cannot mediate the relationship between institutional ownership and dividend policy; however, it partially mediates the effects of public ownership and debt policy on dividend policy